Explicating Mindfulness-based Intervention: Theoretical Insights and Empirical Applications - Gangodawila, Chandima (Journal of International Buddhist Studies, 2021)
Research shows that the effective use of mindfulness-based Intervention brings forth positive consequences such as improving people’s psychological as well as physical health. MBCT (Mindfulness-Based Cognitive Therapy) has remained to be a relatively new and very effective treatment intervention. Therapists who use MBCT combine various cognitive techniques of behavior and well-defined mindfulness strategies to help their clients better understand and, most importantly, effectively manage their concurrent thoughts and emotions. DBT (Dialectical Behavior Therapy) encompasses a comprehensive cognitive-behavioral treatment. Numerous empirical applications have proved DBT to be very effective when used to treat individuals with borderline personality issues. ACT (Acceptance and Commitment Therapy) enables individuals to recognize as well as address challenges that come their way. Besides, ACT leads individuals to become better, not forgetting requiring individuals to execute values-based actions. The main goal of developing this particular treatment approach was to teach individuals that they can better learn and understand effective strategies that will lead them to live healthier and be in a position to cope with normal psychological pain. Practitioners and therapists use mindfulness practices to continually encourage their clients to effectively integrate mindfulness in non-clinical environments and, most importantly, make it part of their lives.